Knowledge of Reproductive Health Issues among the Students of P. N. Campus Pokhara - Palikhe, Amin; Shrestha, Akhila (Janapriya Journal of Interdisciplinary Studies, 2017)
The article entitled "Knowledge of Reproductive Health Issues among the Students of P. N. Campus, Pokhara" has studied to get the knowledge about the reproductive health issues. Reproductive health is one of the important factors of population studies. Several studies have been made concerning the reproductive health issues but there are few research works on the knowledge of reproductive health, especially, in P. N. Campus. The present study attempts to find out knowledge of reproductive health issues among the students in the P. N. Campus. This study was based on the primary information collected from the field survey in P.N. Campus. The sample used for collection of data is random sampling. Basically, both descriptive and analytic research design and simple statistical tools like frequency table, and cross tabulation have been used here. To test the hypothesis, Chi- Square test with contingency table has been presented. Among the total 116 students, 58 percent female and 42 percent male were taken for sample. The median age for the sample population was 23 years. About 31 percent among them were married. This research finds out the knowledge of reproductive health issues like media of knowledge, sources, reproductive health issues areas and level of knowledge among the selected demographic background of respondents. Janapriya Journal of Interdisciplinary Studies Vol. III (December 2014), page: 1-8